Effect of Phenolic Extracts of Peel and Pulp of Tampson Orange with Different Rootstocks on the Inhibition of Soybean Oil Oxidation - M Gharekhani; M Ghorbani; A Gharekhani; A Sadeghi mahoonak; Sh Jabrayili; Y Ghasemi (Institue of Medicinal Plants, ACECR, 2011)
Background: Recently, undesirable symptoms have been reported from the consumption of synthetic antioxidant and in the laboratory animals have been led to carcinogenesis and liver damage. There have been many efforts to replace the synthetic antioxidant with natural antioxidants extracted from plant sources. Objective: The comparison of different rootstock of tompson orange regarding to phenolic and flavonoid compounds in both peel and pulp of the fruit and evaluation of antioxidant activity of selected extracts in soybean oil. Methods: Peels and pulps of four orange rootstocks were examined for their phenolic and flavonoid compounds. In order to investigate the antioxidant activity of selected extracts, different concentrations were added to soybean oil (without antioxidant). Peroxide value (PV) and thiobarbitoric acid (TBA) index were measured at certain period of time and their activities were compared with synthetic antioxidant (butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT)). Results: The results showed that content of phenolic compounds in peel of poncirus rootstock was 31.1 mg GAE/g extract and was higher than other rootstocks and the minimum content of phenolic compounds was measured from pulp part of sour orange rootstock (6.9 mgGAE/g extract). The lowest and highest amount of flavonoid compounds were related to the pulp part of citromela rootstock (1.4 mgQuE/g extract) and the peel part of citrange rootstock (41.3 mgQuE/g extract) respectively. The phenolic and flavonoid contents in peel part were higher than pulp part in all the fruits tested. For the oven test, selective extracts in peel and pulp part of the fruit were poncirus and citromelo rootstocks respectively. More concentrated extracts (600 and 1000 ppm) could be to protect the crude soybean oil from oxidation. The peel extract with 1000 ppm concentration was the only natural extract which was comparable with BHT antioxidant of 200 ppm concentration. Conclusion: The results showed that the phenolic and flavonoid contents were different based on the type of rootstock. Peel and pulp extracts (peel, particularly) can act as a natural antioxidant and can be added to foods after supplementary experiments.